Check Hep C: A Community-Based Approach to Hepatitis C Diagnosis and Linkage to Care in High-Risk Populations. Issue 1 (January 2018) - Ford, Mary M.; Jordan, Ashly E.; Johnson, Nirah; Rude, Eric; Laraque, Fabienne; Varma, Jay K.; Hagan, Holly
Abstract : Context: In New York City (NYC), an estimated 146 500 people, or 2.4% of the adult population, have chronic hepatitis C virus (HCV) infection and half may be unaware of their infection. Despite a 2014 state law requiring health care providers to screen for HCV infection in primary care settings, many high-risk HCV-positive persons are not, and a large proportion of those screened do not receive RNA testing to confirm infection, or antiviral therapies. Objective: The NYC Department of Health's Check Hep C program was designed to increase hepatitis C diagnosis and improve linkage to care at community-based organizations. Design: Coordinated, evidence-based practices were implemented at 12 sites, including HCV antibody testing, immediate blood draw for RNA testing, and patient navigation to clinical services. Results: From May 2012 through April 2013, a total of 4751 individuals were tested for HCV infection and 880 (19%) were antibody-positive. Of antibody-positive participants, 678 (77%) had an RNA test, and of those, 512 (76%) had current infection. Of all participants, 1901 were born between 1945 and 1965, and of those, 201 (11%) were RNA-positive. Ever having injected drugs was the strongest risk factor for HCV infection (40% vs 3%; adjusted odds ratio [AOR] = 19.1), followed by a history of incarceration (18% vs 4%; AOR = 2.2). Of the participants with current infection, 85% attended at least 1 follow-up hepatitis C medical appointment. Fourteen patients initiated hepatitis C treatment at a Check Hep C site and 6 initiators achieved cure. Conclusion: The community-based model successfully identified persons with HCV infection and linked a large proportion to care. The small number of patients initiating hepatitis C treatment in the program identified the need for patient navigation in high-risk populations. Results can be used to inform screening and linkage-to-care strategies and to support the execution of hepatitis C screening recommendations.